NUMERICAL AND EXPERIMENTAL ANALYSIS OF THERMAL AND HYDRAULIC PERFORMANCE OF PERFORATED AND SLOTTED PLATE-FIN HEATSINKS - TARIQ, ADEEL (2020)
An Internal Combustion (IC) engine transfers a considerable amount of heat to the engine walls. An ongoing project of an IC engine with a curved piston and cylinder named Crank-rocker engine (CRE), undergoes overheating using initial 3-fin design. The plate-fin heat sink is used to exchange heat in air-cooled CRE cylinder. Using plate-fins, two improved models of CRE cylinder are proposed, namely curved-fins model and straight-fins model. The improved CRE cylinder has asymmetric heat dissipation and requires a higher heat transfer rate along the smaller curvature of the cylinder. While there is room for improvement in heat transfer rate of plain plate fins, plate fins also face the problems of increased pressure-drop across the heat sink and added weight to the system.